Strategi Pemasaran Umrah Dalam Meningkatkan Jumlah Jamaah di PT. Faza Atama Semesta - Mutiara Farzia; Candra Darmawan (Social Science and Contemporary Issues Journal, 2023)
This research is entitled: "Umrah Marketing Strategy in Increasing the Number of Pilgrims at PT. Atama Phase of the Universe”. The issues discussed in this thesis are: What are the marketing strategies for increasing the number of Hajj and Umrah pilgrims at PT Faza Atama Semesta as well as supporting and inhibiting factors in increasing the number of Hajj and Umrah pilgrims. The objectives of this research are: To determine marketing strategies in increasing the number of Hajj and Umrah pilgrims at PT Faza Atama Semesta and to determine the supporting and inhibiting factors in increasing the number of Hajj and Umrah pilgrims. This research uses qualitative research. The data collection technique in this research uses interview, observation and documentation methods. The theory used in this research is the theory of Philip Kotler. The data analysis technique used in this research is the technique from Miles and Huberman, namely data reduction, data presentation and drawing conclusions. The research results show that the marketing strategy activities carried out by PT. Faza Atama Semesta in increasing the number of congregations has been implemented well. The implementation of marketing strategy activities is carried out well by using a marketing mix, namely: product, price, promotion and place. Marketing strategy planning has several conditions that must be met by a company to be successful in facing competition. This requirement is by trying to achieve a company goal by retaining customers. This means that the company must be able to satisfy and provide what its customers need and want beyond what its competitors provide, while to increase customers the company must be able to read every opportunity that exists through marketing strategies to get new customers.